The Results of the Calculation of the Process and Mechanism of Inhibition of the Compound 2,4,6- Triethanolamine-1,3,5-Triazine in 0.5 M H2So4 Medium Using Thermodynamic and Kinetic Parameters (Eurasian Journal of Physics,Chemistry and Mathematics, 2022)
In this article, the mechanism of inhibition and adsorption isotherms of the compound 4,6-triethanolimine-1,3,5-triazine in a 0.5 M sulfuric acid medium are studied. The values of ΔH* are determined from the slopes of the straight lines and are equal to 17.421 kJ mol–1 for uninhibited 0.5 M H2SO4 and 21.627, 26.231, and 28.379 kJ mol–1 for inhibited solutions of 100 mg/l, 200 mg/l, 250 mg/l, respectively. . The ΔS* values were determined from the points of intersection of the straight lines and are equal to –195.371 J mol–1 K–1 for uninhibited 0.5 M H2SO4 and are equal to –196.275, –197.456 and – 198.954 J mol–1 K–1 for 100 mg /l, 200 mg/l and 250 mg/l corrosion inhibitor TEITA, respectively